PENGARUH MEDIA POWERPOINT TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 3 JAMBANGAN KECAMATAN GEYER TAHUN PELAJARAN 2025/2026 - Fiya Fitri Srirahayu; Elinda Rizkasari; Dite Hastini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using PowerPoint as a learning media on the mathematics learning outcomes of fourth-grade students at SD Negeri 3 Jambangan. The background of this study is the low mathematics achievement caused by conventional teaching methods and the lack of varied learning media. This research employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The subjects of this study were fourth-grade students. Data were collected using achievement tests administered before and after the treatment. The results showed an improvement in students’ learning outcomes after the implementation of PowerPoint media. The average posttest score was higher than the pretest score. This indicates that the use of PowerPoint has a positive effect on students’ mathematics learning outcomes. PowerPoint helps present learning materials in a more engaging, concrete, and understandable way, thereby increasing students’ interest and motivation. In conclusion, the use of PowerPoint as a learning media significantly improves the mathematics learning outcomes of fourth-grade students at SD Negeri 3 Jambangan. Therefore, teachers are encouraged to utilize technology-based learning media to enhance the effectiveness of the teaching and learning process.